Comparative Chemical Profiles of Citrus aurantifolia Essential Oils from South India - Kayikkarakottayil Varkey, Thankachan; Baby, Sabulal; Mathew, Joseph (Asian Journal of Chemistry, 2013)
Essential oils isolated by hydrodistillation of the leaves and fruit peels of Citrus aurantifolia collected from five geographical locations in Kerala viz., Idukky, Thrivanthapuram, Pathanamthitta, Alappuzha and Tamil Nadu were analyzed by gas chromatography-mass spectrometry. Individual essential oil constituents were identified from their mass spectra, NIST database search, linear retention index data and comparison of spectra with literature. Twenty seven to thirty five constituents (99.98-100.03 %) were identified in C. aurantifolia peel oils whereas thirty five to forty constituents (94.59-100.02 %) were identified in its leaf oils. Monoterpene hydrocarbons, oxygenated monoterpenes and sesquiterpene hydrocarbons in peel oils were in the range 71.93-75.05, 10.44-13.81 and 13.24-17.63 %, respectively. Similarly, monoterpene hydrocarbons, oxygenated monoterpenes and sesquiterpene hydrocarbons in leaf oils were 18.66-29.66, 49.24-66.06 and 10.57-20.00 %, respectively. Limonene (37.8-41.93 %), b-pinene (12.78-15.39 %) and a-terpinene (8.02-12.36 %) were the major constituents in peel oils of C. aurantifolia. Limonene (17.33-26.14 %), perilla ketone (0-22.54 %), citronellyl formate (20.76-25.79 %), geranyl acetate (3.65-6.14 %) and (E)-caryophyllene (0-9.72 %) were the major constituents in C. aurantifolia leaf oils. Near similar terpenoid profiles were found in the volatile oils of C. aurantifolia collected from five geographical locations in south India.